Advances in understanding of high-Z material erosion and re-deposition in low-Z wall environment in DIII-D. (24th March 2017) - Ding, R.; Rudakov, D.L.; Stangeby, P.C.; Wampler, W.R.; Abrams, T.; Brezinsek, S.; Briesemeister, A.; Bykov, I.; Chan, V.S.; Chrobak, C.P.; Elder, J.D.; Guo, H.Y.; et al.
Abstract: Dedicated DIII-D experiments coupled with modeling reveal that the net erosion rate of high- Z materials, i.e. Mo and W, is strongly affected by carbon concentration in the plasma and the magnetic pre-sheath properties. Different methods such as electrical biasing and local gas injection have been investigated to control high- Z material erosion. The net erosion rate of high- Z materials is significantly reduced due to the high local re-deposition ratio. The ERO modeling shows that the local re-deposition ratio is mainly controlled by the electric field and plasma density within the magnetic pre-sheath. The net erosion can be significantly suppressed by reducing the sheath potential drop. A high carbon impurity concentration in the background plasma is also found to reduce the net erosion rate of high- Z materials. Both DIII-D experiments and modeling show that local 13 CH4 injection can create a carbon coating on the metal surface. The profile of 13 C deposition provides quantitative information on radial transport due toE × B drift and the cross-field diffusion. The deuterium gas injection upstream of the W sample can reduce W net erosion rate by plasma perturbation. In H-mode plasmas, the measured inter-ELM W erosion rates at different radial locations are well reproduced by ERO modeling taking into account charge-state-resolved carbon ion flux in the background plasma calculated using the OEDGE code.